PENERAPAN PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL DALAM PENGEMBANGAN MORAL ANAK USIA DINI DI RA AR RUM - Hanafiah, Muhammad Ali; Wardati, Laila; Nasution, Leni Masnidar; Anisah, Anisah; Sari, Kumala (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to analyze the implementation of character education based on local wisdom in the moral development of early childhood at RA Ar Rum. The research method employed is a descriptive qualitative approach, with data collected through observation, in-depth interviews, and document analysis. The research subjects include the principal, teachers, parents, and students at RA Ar Rum. The findings indicate that character education based on local wisdom, such as the values of cooperation, politeness, and responsibility, has a significant impact on the moral development of early childhood. Children at RA Ar Rum demonstrate improvement in moral behavior, such as respect for others, responsibility, and cooperation. Despite challenges like the lack of relevant teaching materials and the perception of modern society that tends to overlook local values, the opportunity to integrate traditional values with digital technology offers promising prospects. The conclusion of this study is that character education based on local wisdom is effective in shaping the morals of early childhood, especially when supported by innovation and collaboration from various parties.